A breath of fresh air in foraging theory: The importance of wind for food size selection in a central-place forager - Alma, Andrea Marina (2017)
Empirical data about food size carried by central-place foragers do not often fit with the optimum predicted by classical foraging theory. Traditionally, biotic constraints such as predation risk and competition have been proposed to explain this inconsistency, leaving aside the possible role of abiotic factors. Here we documented how wind affects the load size of a central-place forager (leaf-cutting ants) through a mathematical model including the whole foraging process. The model showed that as wind speed at ground level increased from 0 to 2 km/h, load size decreased from 91 to 30 mm2, a prediction that agreed with empirical data from windy zones, highlighting the relevance of considering abiotic factors to predict foraging behavior. Furthermore, wind reduced the range of load sizes that workers should select to maintain a similar rate of food intake and decreased the foraging rate by ∼70% when wind speed increased 1 km/h. These results suggest that wind could reduce the fitness of colonies and limit the geographic distribution of leaf-cutting ants. The developed model offers a complementary explanation for why load size in central-place foragers may not fit theoretical predictions and could serve as a basis to study the effects of other abiotic factors that influence foraging.